Informal mentorship of new engineers in the workplace - Davis, Pryce; Vinson, Alexandra; Stevens, Reed (2017)
Despite the long history of apprenticeship in engineering (Wilson, 1965), little is understood about the transition from school to work in the modern engineering workforce. How do new engineers gain experience and knowledge while also gaining trust and establishing themselves with more senior engineers and their company? In this work we draw on a large ethnographic study of new engineers in their first year on the job to characterize the role and nature of apprenticeship-like training in the modern engineering workforce. In our analysis, apprenticeship on the job appears to be mostly ad hoc and fleeting with rare instances of direct intentional instruction (as opposed to in-the-moment correction or feedback). Furthermore, learning arrangements between new and more senior engineers are constrained by several factors, including the rigidity of organizational hierarchy, the thoroughness of division of labor, and the senior engineers willingness to actively mentor. For example, we see how new engineers attempt to gain knowledge and experiences from more senior engineers, but are often rebuked due to corporate structure and hierarchy. Yet, at the same time, we see examples of new engineers successfully finding senior co-workers who recognize the importance of training them to navigate these restrictive structures and hierarchies for the benefit of not only the new engineer, but also the senior engineer and the company itself. We find a variety of learning arrangements, including isolated new engineers struggling to find a place in their new work, while also learning new skills, and fully collaborative work between new and senior engineers. We use these findings to suggest ways that engineering schools and companies can help support and enrich the learning of new engineers in the workforce.